Parasite susceptibility in an amphibian host is modified by salinization and predators. (May 2018) - Buss, Nicholas; Hua, Jessica
Abstract: Secondary salinization represents a global threat to freshwater ecosystems. Salts, such as NaCl, can be toxic to freshwater organisms and may also modify the outcome of species interactions (e.g. host-parasite interactions). In nature, hosts and their parasites are embedded in complex communities where they face anthropogenic and biotic (i.e. predators) stressors that influence host-parasite interactions. As human populations grow, considering how anthropogenic and natural stressors interact to shape host-parasite interactions will become increasingly important. We conducted two experiments investigating: (1) the effects of NaCl on tadpole susceptibility to trematodes and (2) whether density- and trait-mediated effects of a parasite-predator (i.e. damselfly) and a host-predator (i.e. dragonfly), respectively, modify the effects of NaCl on susceptibility to trematode infection. In the first experiment, we exposed tadpoles to three concentrations of NaCl and measured parasite infection in tadpoles. In the second experiment, we conducted a 2 (tadpoles exposed to 0 g L −1 NaCl vs. 1 g L −1 NaCl) x 4 (no predator, free-ranging parasite-predator (damselfly), non-lethal host-predator (dragonfly kairomone), and free-ranging parasite-predator + dragonfly kairomone) factorial experiment. In the absence of predators, exposure to NaCl increased parasite infection. Of the predator treatments, NaCl only caused an increase in parasite infection in the presence of the parasite-predator. However, direct consumption of trematodes caused a reduction in overall infection in the parasite-predator treatment. In the dragonfly kairomone treatment, a reduction in tadpole movement (i.e. trematode avoidance behavior) led to an increase in overall infection. In the parasite-predator + dragonfly kairomone treatment, antagonistic effects of the parasite-predator (reduction in trematode abundance) and dragonfly kairomone (reduction in parasite avoidance behavior) resulted in intermediate parasite infection. Collectively, these findings demonstrate that NaCl can increase amphibian susceptibility to parasites, and underscores the importance of considering predator-mediated interactions in understanding how contaminants influence host-parasite interactions. Graphical abstract: Image 1 Highlights: NaCl increased tadpole susceptibility to trematodes. Predators altered the effect of NaCl on tadpole susceptibility to trematodes. Trematode predators reduced trematode abundance, lowering overall infection. Tadpole predators increased trematode infection and removed the effect of NaCl. Studies of contaminants on host-parasite interactions need ecological complexity. Abstract : NaCl increases the susceptibility of amphibian hosts to parasites, but is dependent on presence or absence of other biotic factors (i.e. host and parasite-predators).